ON THE QUESTION OF STUDYING BIBLE AND QURANIC PHRASEOLOGY IN UZBEK LINGUISTICS - Sultonova Shoxista Muxammadjanovna; Sheralieva Shirin Abdisalomovna (Journals Park Publishing, 2024)
The article is devoted to the analysis of the current state of the study of phraseology in Uzbekistan, in particular religious phraseological units based on the material of the Russian and Uzbek languages.
Keywords: theolinguistics, religious phraseology, biblicalism, Koranism, sacred component.